Using Trauma Informed Principles in Health Communication: Improving Faith/Science/Clinical Collaboration to Address Addiction - Clements, Andrea D.; Cyphers, Natalie A.; Whittaker, Deborah L.; Hamilton, Bridget; McCarty, Brett (Frontiers in Psychology, 2021)
Problematic substance use is a pressing global health problem, and dissemination and implementation of accurate health information regarding prevention, treatment, and recovery are vital. In many nations, especially the US, many people are involved in religious groups or faith communities, and this offers a potential route to positively affect health through health information dissemination in communities that may have limited health resources. Health information related to addiction will be used as the backdrop issue for this discussion, but many health arenas could be substituted. This article evaluates the utility of commonly used health communication theories for communicating health information about addiction in religious settings and identifies their shortcomings. A lack of trusting, equally contributing, bidirectional collaboration among representatives of the clinical/scientific community and religious/faith communities in the development and dissemination of health information is identified as a potential impediment to effectiveness. The Substance Abuse and Mental Health Services Administration’s (SAMHSA) tenets of trauma-informed practice, although developed for one-on-one use with those who have experienced trauma or adversity, are presented as a much more broadly applicable framework to improve communication between groups such as organizations or communities. As an example, we focus on health communication within, with, and through religious groups and particularly within churches.